Illustrated Catalogue of European and American Painting and Sculpture : The University of Michigan Museum of Art - Faberman, Hilarie; Wight, Karen (Ann Arbor : The University of Michigan Museum of Art, 1988)
Beckmann, Max ; Moore, Henry ; Avery, Milton ; Albers, Josef ; Avery, Milton ; Dorazio, Piero ; Edlich, Stephen ; Frankenthaler, Helen ; Johnson, Lester ; Kline, Franz ; Koch, John ; Martinez, Ricardo ; Okimoto, Jerry T. ; Saraceni, Remo ; Schmidt, Julius ; Slusser, Jean Paul ; Trova, Ernest ; etc.
boek